2005
DOI: 10.1177/0954008305044901
|View full text |Cite
|
Sign up to set email alerts
|

Viscometric Study of Poly(dimethylsiloxaneb-N-vinylpyrrolidone) in Water Solutions

Abstract: The synthesis and viscometric behavior of poly(dimethylsiloxane-b- N-vinylpyrrolidone) in dilute to extremely dilute water solutions was investigated. The viscometric molecular weights, intrinsic viscosities and critical concentrations which separate the dilute-semi-dilute and dilute-extremely dilute regimes were studied. A dependence between reduced viscosity ηsp /c and concentration for extremely dilute regime was found. The deviation from Huggins dependence is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…On the other hand, the presence of the extremely dilute regime was also confirmed using the dynamic light scattering measurements from the characterization of the conformational changes for various concentrations [22][23][24][25].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…On the other hand, the presence of the extremely dilute regime was also confirmed using the dynamic light scattering measurements from the characterization of the conformational changes for various concentrations [22][23][24][25].…”
Section: Introductionmentioning
confidence: 90%
“…Beside, it is reported that the viscosity measurements showed the presence of anomalies in the viscosity behaviour [16][17][18][19][20][21]. These anomalies are attributed to the adsorption of the sample onto the wall of the capillary and to the change of the real magnitude of molecules below a certain critical concentration [22][23][24][25]. Therefore, the presence of anomalies is contributed to the extremely dilute solution when we consider it as the fourth regime of concentration [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…4,4′-Azobis(4-cyanovaleryl) chloride was synthesized by the reaction of 4,4′-azobiscyanopentanoic acid previously dried by azeotropic distillation from toluene, with phosphorus pentachloride (PCl 5 ) according to the method reported in the literature 39 (Sigma-Aldrich). 1-Vinyl-2-pyrrolidinone (Sigma-Aldrich) was purified before use by vacuum distillation and kept under N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In previous papers [8,[11][12][13][14][15] the synthesis, structural and conformational characterization of some poly(siloxane)s, as well as poly(siloxane-azomethine)s, poly(dimethylsiloxane-b-N-vinylpyrrolidone)s, poly(vinyl-g-dimethylsiloxane)s, and segmented poly (ester-siloxane)-urethane have been described and the characteristics of each of the abovementioned polymers have been discussed.…”
Section: Properties Of Some Poly(siloxane)s For Optical Applications 33mentioning
confidence: 99%